COMMUNITY EMPOWERMENT TO SUPPORT THE IMPROVEMENT OF RURAL COMMUNITY WELFARE IN MANYAR DISTRICT GRESIK - Bhagaskoro Ardhianto Kurniawan (LPPM Universitas Flores, 2026)
The purpose of this community service project is to encourage business ownership and responsible business practices among the residents of Manyar Village, Gresik District, enabling them to establish their own businesses, improve the living conditions of their communities, and compete successfully in a dynamic market environment. The program was implemented through educational activities, training, capacity building, and mentoring. The initial stage involved surveying community conditions in Manyar District to identify the appropriate location and target participants for the program. This was followed by the implementation stage, which included training and capacity-building activities designed to foster an entrepreneurial mindset. The educational materials covered six topics: (1) Basic Concepts of Entrepreneurship, (2) Key Entrepreneurial Characteristics, (3) Creative and Innovative Thinking, (4) Action-Oriented Behaviour, (5) Identifying Personal Hobbies and Transforming Them into Business Ideas, and (6) Ethical Entrepreneurship. In addition to the training sessions, participants received mentoring and hands-on practice opportunities, including the development of business plans using the Business Model Canvas framework and the presentation of their business ideas. The final stage consisted of monitoring and evaluation activities to assess the effectiveness and success of the program. The results indicated increased entrepreneurial motivation, greater self-confidence in starting or expanding businesses, and enhanced ability to apply entrepreneurial knowledge after gaining an understanding of the importance of an entrepreneurial mindset. As a result of participating in this Community Service Program, community members developed an entrepreneurial perspective that is expected to contribute to improving the financial well-being of local families.